Guía para la planificación de la gestión ambiental de obras civiles menos a 5000 metros cuadrados de apartamentos nuevos para vivienda tipo VIS en Bogotá D.C. (2020)
This document aimed at the elaboration of a guide for environmental management, which focused on the planning, execution, monitoring and control for obtaining quarry material, the disposal of quarry material waste and the maintenance and supervision of construction machinery. This guide should be part of every civil work in Bogotá D.C. Both, the final document and the guide contain all the norms and laws that apply to the area of environmental management in civil works of less than 5,000 square meters of new apartments for social interest housing in Bogotá D.C.